(untitled) (Journal of Intellectual Property Rights (JIPR), 2023)
The Coronavirus disease 2019 or COVID-19, pandemic has transpired disastrous effects in the world in multiple forms ranging from the high death tolls to the steep fall in global economy. Even so, it had managed to provide a silver lining in the form of unanimity of researchers from several disciplines, who united to contribute blood, sweat and tears to present to the world the miracle of science- vaccines. One can only imagine the extent of investment which has gone into development of the few vaccines we have today. In fact the research continues to be in full swing, with the hope and zest to better. While every country fights the pandemic with vigor, it is the pharmaceutical R&D which is expected of breakthrough discoveries as a solution. Where the pressure to succeed is tremendous, millions invested and no option to fail is it not justified to expect and deserve patent for the same. This paper will dwell into the justification of patent over Covid-19 vaccines, the ongoing debate over patent waiver and analyze whether the waiver will in fact facilitate greater access and affordability of vaccines or prove to be an impediment for global supply.